(untitled) (CAHIERS MAGELLANES-NS, 2024)
Rapid urbanization and industrialization have significantly boosted cement production, which has resulted in significant environmental contamination. The control of the significant carbon footprints has been the major worldwide concern in relation to the production of cement. Utilizing ecofriendly cementitious substances in design of structures has proven to be a practical solution to this environmental issue. Through use of cementitious substances, which, albeit partially, can substitute cement, must therefore be further examined. In this research, two of these cement replacement materials, namely, Meta-kaolin (MK) and Marble-Powder (MP) - have been examined. In this work, Meta-kaolin (MK) and Marble-Powder (MP)have been prepared as partial substitutes for cement in M65 grade High Performance Concrete. To improve the workability, a polycarboxylate-ether-based superplasticizer has been utilized. The mechanical strength (compressive, split tensile and flexural strength) of the test material, which was casted and allowed to be cured for 7, 28, and 56 days at room temperature, was determined in accordance with Indian guidelines. The ideal mixture of high-performance-concrete created in this way complied with Indian regulations, and the blend of cement + 12.5% Marble Powder + 7.5% Metakaolin showed the best compressive strength and flexural strength and 0 % Marble Powder + 20 % Metakaolin showed the best split tensile strength after 56 days of curing. Metakaolin (MK) and Marble Powder (MP) are suggested as partial cementitious materials since their usage in lesser amounts has boosted the strength of concrete.